2005
DOI: 10.1002/art.21421
|View full text |Cite
|
Sign up to set email alerts
|

Very low‐dose prednisolone in early rheumatoid arthritis retards radiographic progression over two years: A multicenter, double‐blind, placebo‐controlled trial

Abstract: Objective. To assess the effect of 5 mg/day prednisolone on disease progression in patients with early rheumatoid arthritis (RA) receiving standardized diseasemodifying antirheumatic drug (DMARD) therapy.Methods. Patients with active RA of <2 years' duration were randomly assigned in a double-blinded manner to receive prednisolone or placebo while starting concomitant DMARD therapy (gold sodium thiomalate or methotrexate). Hand and foot radiographs were taken at baseline and at 6, 12, and 24 months and were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
165
1
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(194 citation statements)
references
References 36 publications
13
165
1
15
Order By: Relevance
“…The main objective of this multicenter study was to evaluate, with a transversal and longitudinal approach, in real life, the prevalence and incidence of osteoporotic fractures and to identify their major determinants in a sample of patients with ed that the treatment with disease-modifying anti-rheumatic drugs (DMARDs) in association with GCs may induce high and persistent remission rates (5). This disease-modifying effect of GCs is supported by different studies (5)(6)(7)(8)(9)(10)(11)(12). In addition, the results also showed that GCs have an action in retarding the progression of erosive joint damage in early RA (prior to any joint damage) and a control of disease activity (5)(6)(7)(8)(9)(10)(11)(12).…”
supporting
confidence: 55%
“…The main objective of this multicenter study was to evaluate, with a transversal and longitudinal approach, in real life, the prevalence and incidence of osteoporotic fractures and to identify their major determinants in a sample of patients with ed that the treatment with disease-modifying anti-rheumatic drugs (DMARDs) in association with GCs may induce high and persistent remission rates (5). This disease-modifying effect of GCs is supported by different studies (5)(6)(7)(8)(9)(10)(11)(12). In addition, the results also showed that GCs have an action in retarding the progression of erosive joint damage in early RA (prior to any joint damage) and a control of disease activity (5)(6)(7)(8)(9)(10)(11)(12).…”
supporting
confidence: 55%
“…A study of low-dose GC reported weight gain in fewer (4/93) patients [ 77 ]. Weight gain contributes to the risk of GC-induced DM [ 74 ]; EULAR and the BSR recommend monitoring weight during follow-up [ 15 , 80 , 81 ].…”
Section: Weight Gainmentioning
confidence: 99%
“…Regarding low-dose GC, the existing data appear reassuring [ 78 , 90 , 91 ] and it is important to bear in mind the benefits of effectively treating disease; depression may be ameliorated by low-dose GCs in RA [ 77 ]. In contrast, patients receiving high-dose GCs appear more likely to experience neuropsychiatric symptoms, although confounding by indication limits interpretation of existing data.…”
Section: Neuropsychiatricmentioning
confidence: 99%
“…Clinical effectiveness and less joint damage were demonstrated. Subsequently a number of studies from Europe were published examining low-dose prednisone versus placebo in early RA showing similar results, including less joint damage (13)(14)(15)(16). These studies utilized low single-morning doses of 5 mg, 7.5 mg, and 10 mg per day, all with comparable results.…”
Section: To the Editormentioning
confidence: 98%